2000
DOI: 10.1007/s004240000394
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide has no beneficial effects on ion transport defects in cystic fibrosis human nasal epithelium

Abstract: Nitric oxide (NO) has been reported to activate Cl- secretion via the cystic fibrosis transmembrane conductance regulator (CFTR) and inhibit epithelial Na+ absorption mediated by amiloride-sensitive epithelial Na+ channels (ENaC). These ion transport systems are defective in cystic fibrosis (CF): Cl- secretion by CFTR is impaired and Na+ absorption by ENaC is dramatically increased. By activating CFTR and depressing ENaC, NO is a potentially beneficial therapeutic agent for ion transport defects in human CF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Application of 100 M GSNO and SNAP to patch-clamp recording solution did not significantly alter ENaC P o in ATII cells. This finding is similar to the results obtained by Rückes-Nilges et al (38), who showed that NO released from spermine NONOate had no inhibitory potency on the human nasal epithelium. The different effects of NO donors in renal epithelial cells and in the lung epithelium may pertain to the slow half-lives of the donors used in the studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Application of 100 M GSNO and SNAP to patch-clamp recording solution did not significantly alter ENaC P o in ATII cells. This finding is similar to the results obtained by Rückes-Nilges et al (38), who showed that NO released from spermine NONOate had no inhibitory potency on the human nasal epithelium. The different effects of NO donors in renal epithelial cells and in the lung epithelium may pertain to the slow half-lives of the donors used in the studies.…”
Section: Discussionsupporting
confidence: 92%
“…Stoos and colleagues (40,41) showed that acetylcholine-induced NO release from endothelial cells, as well as addition of the NO donor spermine NONOate, inhibited Na ϩ reabsorption in CCD cells. Rückes-Nilges et al (38) reported that 1 mM of sodium nitroprusside clearly inhibited amiloride-sensitive Na ϩ reabsorption in Xenopus kidney A6 distal nephron cell lines. However, in their study, the NO donors sodium nitroprusside and spermine NONOate did not alter either the amiloridesensitive or the amiloride-insensitive portions of I sc in primary cultures of human nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…Contradictory evidence of the effect of NO on CFTR channel function and biogenesis has been reported. For example, NO has been shown to activate CFTR in human T lymphocytes (51), while Ruckes-Nilges et al (52) reported that NO had no effect on CFTR or any other chloride channel activation in primary nasal epithelial cells. GSNO, on the other hand, was found to activate chloride channels in lung epithelial cells (53).…”
Section: Fig 4 Gsno Promotes the Maturation And Function Of ⌬F508mentioning
confidence: 99%
“…On the other hand, there is a lack of consensus on measurement techniques, which consequently lead to different findings of nNO concentrations in different airway illnesses, such as sinusitis [10,13], polyposis nasi [8,10] and (allergic) rhinitis [9,[14][15][16]. Exceptions are cystic fibrosis (CF) [17][18][19][20][21][22] and primary cilliary dyskinesia [23][24][25][26]. It is well established that the nNO levels in these patients are extremely low and are independent of the measurement methods used.…”
mentioning
confidence: 99%